Quality and Nutritional Evaluation of Regina Tomato, a Traditional Long-Storage Landrace of Puglia (Southern Italy) - Massimiliano, Renna; Miriana, Durante; Gonnella, Maria; Buttaro, Donato; D’Imperio, Massimiliano; Mita, Giovanni; Serio, Francesco (My University, 2018)
Regina tomato, a locally cultivated Italian landrace, is listed as an item in the ‘List of Traditional Agri-Food Products’ of the Italian Department for Agriculture and itemised as ‘Slow Food presidium’ by the Slow Food Foundation. It is classified as a long-storage tomato since it can be preserved for several months after harvest thanks to its thick and coriaceous skin. Three ecotypes were investigated for main physical and chemical traits both at harvest and after three months of storage. Experimental results indicate that this tomato landrace has a qualitative profile characterized by high concentrations of tocopherols, lycopene and ascorbic acid (maximum 28.6 and 53.7 mg/kg fresh weight, FW, and 0.28 mg/g FW, respectively) even after a long storage time, together with lower average Total Soluble Solids. The initial and post-storage contents of the bioactive compounds changed at a different rate in each ecotype (i.e., in Monopoli Regina tomato the highest content of α-Tocopherol, thereafter reduced to the same level of the other two ecotypes). These results indicate unique and unmistakable features of this long-storage tomato, closely linked to the geographic origin area that include both natural (available technical inputs) and human (specific cultural practices) factors.
Keywords: ecotypes; geographical origin area; HPLC analyses; long storage time; Solanum lycopersicum L.; heirloom